Teacher Trainees' Perceptions of Health Literacy Integration in Classrooms - Sahputri, Juwita; Azhari, Teuku; Mukhlis, Mukhlis (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2025)
Health literacy plays a critical role in education. Incorporating health literacy into educational programs improves students’ ability to make knowledgeable health decisions and supports a better and healthier lifestyle. This study aims to unveil the attitudes, preparation, and obstacles or resources that teacher-training students have while including health literacy in their lessons. It seeks to ascertain their opinions on encouraging health-conscious classrooms, their level of preparedness to use health literacy, and the obstacles or facilitators to its successful use. This study emphasizes the value of incorporating health literacy into teacher preparation programs, stresses the roles that educators play in raising health awareness, and makes recommendations for changes to educational policies. With a focus on the senior year of Indonesian Language Education majors at the Faculty of Education, this qualitative study incorporated semi-structured interviews with five Lecturers and fifteen randomly selected students from Indonesian Language Majors. The study found that real-world health subjects encourage engagement, and health literacy improves student well-being by encouraging healthy practices that improve focus and learning. A lack of resources can make students less confident when researching content, therefore they require courses that are structured and have defined strategies. Integration is difficult due to time restrictions, but tools such as online resources and guest lectures, as well as cross-disciplinary inclusion, can promote successful learning.